2018
DOI: 10.1093/femsle/fny260
|View full text |Cite
|
Sign up to set email alerts
|

The qualified presumption of safety assessment and its role in EFSA risk evaluations: 15 years past

Abstract: Microorganisms are intentionally added at different stages of the food and feed chain (food or feed additive, novel food or plant protection product) and are subjected to regulation and safety assessment by the European Food Safety Authority. Safety evaluation is based on application dossiers for market authorisation to the European Commission. The qualified presumption of safety (QPS) concept was developed in 20031 to provide a harmonised generic safety pre-appraisal of the above microorganisms. Unambiguously… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(26 citation statements)
references
References 13 publications
0
26
0
Order By: Relevance
“…In this study, we have shown the potential sleep-improving effects of PS150 TM , which has also been demonstrated as a psychobiotic capable of alleviating abnormal behaviors induced by mild chronic stress in rats [16]. The use of PS150 TM as a dietary supplement is generally considered as safe, since PS150 TM is classified as the species L. fermentum, with the qualified presumption of safety (QPS) status suggested by the European Food Safety Authority [61]. One major limitation of this study is the non-use of polysomnography; moreover, possible interactions between pentobarbital and probiotics cannot be excluded.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we have shown the potential sleep-improving effects of PS150 TM , which has also been demonstrated as a psychobiotic capable of alleviating abnormal behaviors induced by mild chronic stress in rats [16]. The use of PS150 TM as a dietary supplement is generally considered as safe, since PS150 TM is classified as the species L. fermentum, with the qualified presumption of safety (QPS) status suggested by the European Food Safety Authority [61]. One major limitation of this study is the non-use of polysomnography; moreover, possible interactions between pentobarbital and probiotics cannot be excluded.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to synthetic, there are simple biosynthetic procedures of GABA with high efficiency and environmental compatibility 10 . The promising source of GABA for the potential treatment of exacerbated inflammation are probiotic bacteria, considering the fact that main producers of GABA belong to lactic acid bacteria (LAB) 11 which have the "Qualified Presumption of Safety" (QPS) status 12,13 .…”
mentioning
confidence: 99%
“…Protection of public health against the adverse effects of mTG should be of the utmost importance. The FDA and the European Food Safety Authority recently published the regulatory demands and follow-ups on the GRAS status of food additives and microbial enzyme usage by the food industries [107][108][109][110]. Because of the enzyme mTG and its gliadin cross-linked complexes' potential pathogenic activities, summarized in Figure 1, the authors urge the worldwide food safety regulatory authorities to analyze the current knowledge and consider the alleviation of the GRAS status from this heavily used food additive.…”
Section: Should Microbial Transglutaminase Be Declared As a Public Hementioning
confidence: 99%